Solidarity in EU law : legal principle in the making - Biondi, Andrea; Dagilytė, Eglė; Küçük, Esin (Edward Elgar Publishing, 2018)
The European Union has evolved from a purely economic organisation to a multi-faceted entity with political, social and human rights dimensions. This has created an environment in which the concept of solidarity is gaining a more substantial role in shaping the EU legal order. This book provides both a retrospective assessment and an outlook on the future possibilities of solidarity's practical and theoretical meaning and legal enforcement in the ever-changing Union. Solidarity in EU Law examines the less explored topics of the European solidarity debate, such as the practical enforceability of solidaristic obligations in EU law and non-EU investment into the economic services of general interest via 'golden shares', at the same time contributing to the ongoing debates on solidarity in the context of European financial crisis and immigration, asylum and border checks. The expert editors bring these fields together to create a cohesive analysis of the ways in which solidarity is becoming a principle of EU constitutional law rather than merely a philosophical or political concept. Unique and insightful, this book is ideal reading for European law academics and research students. Its exploration of the current laws on solidarity regarding asylum and human rights would also benefit advisors in non-governmental organisations, as well as legal advice professionals working with EU citizens.